2021
DOI: 10.1007/s00264-021-05083-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative prospective randomized study of minimally invasive transpiriformis approach versus conventional posterolateral approach in total hip arthroplasty as measured by biology markers

Abstract: Background Minimally invasive surgery is becoming increasingly common, but evidence of the advantages of the minimally invasive transpiriformis approach in total hip arthroplasty is limited. Therefore, our single-centre randomized controlled trial evaluated the benefits of this approach versus the posterolateral approach. Methods Forty-nine patients undergoing the minimally invasive transpiriformis approach and 57 patients undergoing the posterolateral app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…We determined the serum levels of IL-6, CRP, and CK between patients 24 h after extra-articular distal humeral APLCP through posterior approaches and LPO. IL-6, CRP, and CK are three biology markers and their reductions were used to reflect less muscle damage caused by invasive orthopaedic surgery [ 20 ]. It was found that although the serum levels of IL-6, CRP, and CK were elevated 24 h after surgery, the patients receiving implantation of APLCPs through a posterior approach exhibited lower serum levels of IL-6, CRP, and CK compared to LPO, suggesting extra-articular distal humeral APLCP through posterior approaches leads to attenuated inflammatory response, preventing patients from soft tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…We determined the serum levels of IL-6, CRP, and CK between patients 24 h after extra-articular distal humeral APLCP through posterior approaches and LPO. IL-6, CRP, and CK are three biology markers and their reductions were used to reflect less muscle damage caused by invasive orthopaedic surgery [ 20 ]. It was found that although the serum levels of IL-6, CRP, and CK were elevated 24 h after surgery, the patients receiving implantation of APLCPs through a posterior approach exhibited lower serum levels of IL-6, CRP, and CK compared to LPO, suggesting extra-articular distal humeral APLCP through posterior approaches leads to attenuated inflammatory response, preventing patients from soft tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study, it was found that IL-6 < 15 pg/ml resulted in better HHS values on day 14 (p=0.016; OR=6.3 (1.325-29.945); 95% CI), as well as day 30 (p=0.015; OR=1.4 (1.005-1.950); 95% CI) after bipolar HA surgery with the percentage of good HHS values of 77.8% (H-14) and 100% (H-30), while the levels of IL-6 15 pg/ml resulted in better HHS values of 35.7% (H-14) and 71.4% (H-30). In a study conducted by [9] surgical techniques with minimally invasive techniques have lower levels of IL-6 and have better HHS. The mean levels of IL-6 obtained were 4.67 + 1.87.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of included studies are presented in Table I. Seventeen studies including 3,551 patients met the inclusion criteria [10][11][12][13]17,[19][20][21][22][23][24][25][26][27][28][29][30] . The number of patients per study ranged from 20 to 1,341, with a mean age range of 51 to 74 years (Table I).…”
Section: Quality Assessment and Methodologymentioning
confidence: 99%
“…One hundred eighty-one studies were excluded after reviewing duplications using EndNote, and 207 articles were screened by title and abstract, of which 52 articles were eligible for full-text screening. Ultimately, 17 qualifying articles were selected [10][11][12][13]17,[19][20][21][22][23][24][25][26][27][28][29][30] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation